Optimization of high hardness perforated steel armor plates using finite element and response surface methods - EKİCİ, BÜLENT (TAYLOR & FRANCIS INC, 2017)
In this article, finite element simulations and response surface method are used to optimize perforated plate parameters for ballistic protection. After statistically validating the relationship between residual velocity and geometric parameters, a response optimizer was used to find the best combination of design parameters to stop a threat with less areal density. Finally, the optimized solution was checked both numerically and experimentally to show the effectiveness of the developed methodology. The weight is decreased by 28% when compared with monolithic steel armor having the same antiballistic performance.
Keywords: 7.62 mm armor piercing bullet; ballistic simulation; high hardness armor; Johnson-Cook material model; perforated plates; response surface method; BALLISTIC RESISTANCE; IMPACT; PROJECTILE; BEHAVIOR; HOLES